Willingness to Pay and Factors Affecting the Income of Rice and Corn Farmers in the Use of Superior Seeds in North Raman Sub District: IPB University (Jurnal Ekonomi dan Kebijakan Pembangunan, 2022)
One of the agricultural sub-sectors is food crops, such as rice and corn which is the main sources of carbohydrates. The factor of productivity’s food crops is due to the use of seeds. Raman Utara is a region that has the potential to have high productivity in rice and corn. However, the quality of seeds in the region has a problem that has an impact on the low productivity of rice and corn. Superior seed is the best solution to increase productivity but the high price will make it difficult for farmers to buy them. So farmers' willingness to pay for certified superior seed is one of the problems because of low farmer’s income. The purpose of this study is to analyze farmers' income and willingness to pay for using seeds. The data were used in the study from 100 respondents with 60 farmers of rice and 40 farmers of maize. Data was collected using the purposive sampling method. Multiple linear regression (OLS), logistic regression, and contingent valuation methods were used as analysis methods. The results of the study showed that the variable of land area has negative and significant and the fertilizer’s variable has positive and significant to the selection of hybrid and inbred rice seeds. The other results showed that the variable of revenue has positive and significant and the fertilizer and labor variables have negative and significant to the income of corn farmers. The willingness to pay farmers for seed is more than the actual market price.